Penyuluhan Etika Bersosial Media (Facebook) Pada Karang Taruna RW 17 Di Kelurahan Pancoran Mas Kota Depok - Whendasmoro, Raditya Galih; Sharyanto, Sharyanto (LPPM Universitas Bung Karno, 2022)
The development of information technology is currently very rapid from all aspects, one of which aims to facilitate the sharing of data and information without time and place limits. One of the applications in the purpose of sharing data and information in general is the use of social media, but with all the conveniences available, of course you have to stay alert and need to be wise in using social media to stay safe. This community service activity is in the form of social media ethics counseling in the Pancoran Mas sub-district environment, Depok city. This community service activity aims to provide information in the form of counseling on ethics in social media, so that social media can be used as its main function, namely sharing data and information and possibly also for business activities. This community service activity is carried out using the method of delivering material on the substance of the activity, followed by practice in operating one of the social media, namely Facebook and Facebook. operating one of the social media, namely Facebook and evaluating the participants to find out to what extent they have absorbed the training material that has been given, especially ethics in social media on Facebook. Based on the results of the graphic design skills training activities, it is known that the participants can understand, use the facilities and functions available on Facebook social media with good ethics.